Flexural performance criteria for steel fibre reinforced concrete – an experimental investigation - Jain, Kranti; Singh, Bhupinder (Journal of Structural Engineering, 2024)
Although steel fibre reinforced concrete (SFRC) is widely used for non-structural applications, until recently its use as structural concrete has been limited because of a lack of relevant guidelines in current design codes. As a noteworthy step towards encouraging the use of SFRC for structural applications, the 2008 ACI Building Code allows the use of deformed steel fibres in volume fractions greater than 0.75% as minimum shear reinforcement in normal strength concrete beams provided that the SFRC satisfies the code prescribed flexural performance criteria. This study discusses the ACI code flexural performance criteria which have been used to appraise results of an experimental investigation of the flexural performance of SFRC mixtures containing hooked end or crimped fibres tested in four-point bending as per ASTM C1609. The tests showed that mixtures containing the 60 mm long hooked-end fibres satisfied the ACI code prescribed flexural performance criteria whereas the mixtures containing the other fibre types were found to be unsuitable for flexural applications. It is suggested that the use of limit of proportionality instead of the first peak load would result in a more objective evaluation of flexural performance of steel fibrous concrete.